Find X: Track Down Missing People Using MTCNN and FaceNet - Mistry, Hemant; Koli, Rangel Anselm; Kotian, Deep; More, Rushi; Tuscano, Grinal (Indian Journal of Computer Science, 2024)
Every single day, thousands of missing people cases are registered with the police. Thousands of people go missing due to many reasons such as kidnapping, human trafficking, mental health issues, miscommunication, misadventure, domestic violence, or becoming victims of a crime. It is important to track and rescue these people efficiently and safely. Over the past few years, the number of cases of missing persons has increased exponentially. Locating missing people is a very tedious and laborious task for the police department as the police have to manually go and search for these missing people.Â There is an acute necessity to help reduce the amount of time taken to track and rescue these missing people. The proposed system, "FindX," can be used to locate missing people significantly faster than the existing traditional methods. This system uses MTCNN (Multi-Task Cascaded Convolutional Neural Networks) for detecting facial landmarks and the FaceNet algorithm to match images.